Pengaruh Kualitas Pelayanan, Kualitas Produk Terhadap Minat Beli Ulang Pengguna E-Commerce Shopee Dengan Kepuasan Pelanggan Sebagai Variable Intervening Pada Masyarakat Kota Bandar Lampung - Intan Regita Cahyani; Yateno; Ratmono (Universitas Muhammadiyah Metro, 2025)
This study aims to find out whether service quality and product quality affect repurchaseintention with customer satisfaction as the intervening variable. This type of researchconducted in research is to use quantitative research. The population in this study wereSprighill residents, Bandar Lampung City, totaling 140 people who actively use Shopee.Determining the number of samples using the Sovlin formula with an error margin of 5%, asample of 50 was obtained. The data collection technique used was interviews andquestionnaires. data analysis used included validity test, reliability test, normality test,linearity test, homogeneity test. Data analysis in this study used Regression Analysis ofMediating Variables with the Causal Step Method with the help of the SPSS version 25.0application. Service quality, product quality has a positive and significant impact oncustomer satisfaction with Shopee users in the Bandar Lampung City Community. ProductQuality, Service Quality have a positive and significant impact on the repurchase intention ofShopee users in the Bandar Lampung City Community. Customer satisfaction has a positiveand significant influence on the repurchase intention of Shopee users in the Bandar LampungCity Community